Highly selective hydrodeoxygenation of wood pallet sawdust pyrolysis oil to methyl phenol derivatives using cobalt and iron on activated carbon supported catalysts - Quoc Khanh Tran; Hoang Vu Ly; Thuan Anh Vo; Hyun Tae Hwang; Jinsoo Kim; Seung-Soo Kim (Energy Conversion and Management: X, 2022)
The catalytic hydrodeoxygenation (HDO) processes for upgrading pyrolysis bio-oils from wood pallet sawdust (WPS) were studied using activated carbon (AC) as a support of mono- (Co/AC and Fe/AC) and bi-metallic (Co-Fe/AC) catalysts. The effects of the reaction temperature and hydrogen pressure on products and high heating value (HHV) were systematically investigated. At 350 °C and 60 bar, 20 wt% Co/AC showed the highest liquid yield (70.46 wt%) along with HHV of 34.22 MJ/Kg. Among the tested bimetallic catalysts, comparable liquid yield (68.85 wt%) and HHV (34.16 MJ/kg) were achieved with 20 wt% 4Co-1Fe/AC catalyst. Methyl phenol derivatives were found to be the main component in upgraded bio-oil. The carbon number of the upgraded bio-oil was mainly distributed in C5–C11 fraction, especially with the C8 component (20.40 wt%). The catalysts were deactivated by the formation of carbonaceous compounds on the external surface, oxidation of metal species, and blocking of active sites on catalysts.